Pacing behavior of elite youth athletes: Analyzing 1500-m short-track speed skating - Menting, S. G. P.; Konings, M. J.; Elferink-Gemser, M. T.; Hettinga, F. J. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To gain insight into the development of pacing behavior of youth athletes in 1500-m short-track speed-skating competition. Methods: Lap times and positioning of elite short-track skaters during the seasons 2011/2012-2015/2016 were analyzed (N=9715). The participants were grouped into age groups: under 17 (U17), under 19 (U19), under 21 (U21), and senior. The difference between age groups, sexes, and stages of competition within each age group were analyzed through a multivariate analysis of variance (P<.05) of the relative section times (lap time as a percentage of total race time) per lap and by analyzing Kendall tau-b correlations between intermediate positioning and final ranking. Results: The velocity distribution over the race differed between all age groups, explicitly during the first 4 laps (U17: 7.68% [0.80%], U19: 7.77% [0.81%], U21: 7.82% [0.81%], and senior: 7.80% [0.82%]) and laps 12, 13, and 14 (U17: 6.92% [0.14%], U19: 6.83% [0.13%], U21: 6.79% [0.14%], and senior: 6.69% [0.12%]). In all age groups, a difference in velocity distribution was found between the sexes and between finalists and nonfinalists. Positioning data demonstrated that youth skaters showed a higher correlation between intermediate position and final ranking in laps 10, 11, and 12 than seniors. Conclusions: Youth skaters displayed less conservative pacing behavior than seniors. The pacing behavior of youths, expressed in relative section times and positioning, changed throughout adolescence and came to resemble that of seniors. Pacing behavior and adequately responding to environmental cues in competition could therefore be seen as a self-regulatory skill that is under development throughout adolescence.